Significant decrease in liver stiffness detected by two dimensional shear-wave elastography after treatment with direct-acting antiviral agents in patients with chronic Hepatitis C - Serkan Yaraş; Orhan Sezgin; Enver Üçbilek; Osman Özdoğan; Engin Altıntaş (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Two-dimensional shear-wave (2D-SWE) elastography is one of the noninvasive methods for the evaluation of liver fibrosis. The purpose of this study is to investigate the changes in liver stiffness (LS) by employing 2D-SWE as well as its correlation with noninvasive fibrosis markers in patients with chronic hepatitis C (CHC), who are undergoing direct-acting antiviral (DAA) therapy.Materials and Methods: The researchers included all the patients with CHC who are scheduled for DAA treatment in this study. 2D-SWE measurements were performed at baseline, end of treatment (EOT), and 12 weeks after the treatment. According to the latest EFSUMB guidelines, elastography measurements were performed during the ultrasonographic evaluation and recorded in kilopascals (unit). The correlation between biochemical and viral responses, and noninvasive fibrosis scores (FIB-4, AST-to-platelet ratio index (APRI)) was also evaluated.Results: This study employed 230 patients who underwent treatment with DAAs between September 2016 and September 2017. However, 131 patients were able to complete the study, of which 48 (36.6%) were male and 83 (63.4%) were female. The mean age was 65.0 (±11.18) years. Both EOT and sustained viral response (SVR) had the same rate of 99.2% (130/131). The SWE measurement (mean) values at pretreatment, EOT, and 12 weeks after treatment was 12.92, 10.45, and 9.07 kPa, respectively (p<0.05), whereas the APRI scores were 0.76, 0.39, and 0.30, respectively (p<0.05). Additionally, the FIB-4 scores at pretreatment, EOT, and 12 weeks after treatment were 2.98, 2.43, and 2.03, respectively (p<0.05). The results of liver stiffness measurements (LSM) were similar in all the groups of cirrhotic, noncirrhotic, treatment-experienced, and treatment-naive patients.Conclusion: DAA treatments in the patients with CHC led to almost a complete SVR and a considerable decrease in LS in a short time.Cite this article as: Yaraş S, Sezgin O, Üçbilek E, Özdoğan O, Altıntaş E. Significant decrease in liver stiffness detected by two dimensional shear-wave elastography after treatment with direct-acting antiviral agents in patients with chronic Hepatitis C. Turk J Gastroenterol 2020; 31(2): 142-7.